An improved and updated 20-years air pollution exposure dataset for Germany 2003-2022 (APExpose_DE v6)Zenodo - Alexandre Caseiro; Erika von Schneidemesser (Data in Brief, 2025)
The link between exposure to polluted air and the outcome of diseases (e.g., cardio-vascular diseases, COVID-19) has been established. Nevertheless, research on the quantification of the relationship is still relevant today. Quantifying the link between the ambient atmospheric concentrations of pollutants and the outcome of diseases requires knowledge on the levels of the pollutants through time at various scales. In the present work, an improved and updated version of the APExpose_DE dataset is described. The dataset provides air pollution metrics at the yearly time resolution and at the spatial resolution of the NUTS-3 level, corresponding to the Landkeis/Kreisfreie Stadt in Germany. The dataset evolved from its initial form by expanding the years covered and by refining the gap-filling methodology. The dataset can serve as input to, e.g., observational studies.